1999
DOI: 10.1002/jlb.65.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Different in vivo tolerogenicity of MHC class I peptides

Abstract: The efficacy of MHC class I-derived peptides to induce tolerance was tested in a cardiac transplantation model. Two 25-mer peptides from the polymorphic region of the DA class I molecule (RT1.Aa) were synthesized by F-moc chemistry and injected intrathymically or intraperitoneally into LEW (RT1.1) responder animals. Intrathymic treatment of the recipient animals with peptide 1 (residues 56-80) accompanied by intraperitoneal treatment with peptide 4 (residues 96-120) led to indefinite survival of allogeneic DA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…12,13,28 On this basis, several HLA-B7-derived peptides covering residues 56 to 120 were synthesized using the FMOC technique, as we previously described in more detail. 29 Peptides synthesized and used in these experiments are shown on the sequence alignment in Figure 1 and Table 1.…”
Section: Synthesis and Fitc Conjugation Of Mhc-derived Allopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,28 On this basis, several HLA-B7-derived peptides covering residues 56 to 120 were synthesized using the FMOC technique, as we previously described in more detail. 29 Peptides synthesized and used in these experiments are shown on the sequence alignment in Figure 1 and Table 1.…”
Section: Synthesis and Fitc Conjugation Of Mhc-derived Allopeptidesmentioning
confidence: 99%
“…[9][10][11] In other studies, class I-and class II-derived allopeptides were used to induce tolerance. [12][13][14] By studying a series of rat-derived synthetic allo-MHC peptides, immunodominant regions of allogeneic MHC molecules that modulate graft survival were identified. 13 These studies revealed that some regions of MHC class I molecules are not immunogenic and do not modulate alloresponses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous approaches towards manipulation of T-cell differentiation have used intrathymic injection of antigens, as proteins [Fandrich et al, 1999;Ilan et al, 1996;Oluwole et al, 1999], cells [Behara et al, 1992] or adenoviruses [DeMatteo et al, 1995;Ilan et al, 1996], leading to transient expression of the foreign protein and reduction of antigen-specific immune responses. The concept of targeting thymus to minimize immune responses have been proposed for many years, however the clinical experience is still lacking.…”
Section: Induction Of Central Tolerancementioning
confidence: 99%
“…The spleen and mesenteric lymph nodes were removed aseptically, transferred to sterile phospho-buffered saline (PBS) at 4 o C and pressed through a nylon cell strainer to produce a single cell suspension. Lymphocytes were isolated by Ficoll 400/ Uropolinum 75% density -gradient in centrifugation for 15 min at 4 o C [12].…”
Section: Isolation Of Lymphocytesmentioning
confidence: 99%